COVID-19: Indian Society of Neuroradiology (ISNR) Consensus Statement and Recommendations for Safe Practice of Neuroimaging and Neurointerventions. Issue 5 (October 2020) - Sebastian, Leve Joseph Devarajan; Ahuja, Chirag; Sekar, Sabarish; Senthilvelan, Santhakumar; Kulanthaivelu, Karthik; Lanka, Vivek; Goel, Vinay; Mohapatra, Sarita; Jain, Chirag; Senthilkumaran, S.; Garg, Ajay; Balasundaram, Parthiban; et al.
The ongoing COVID-19 pandemic has forced every radiology set-up to evolve and formulate guidelines for day-to-day functioning. The sub-speciality of neuroradiology, both diagnostic and neuro-intervention, forms a very important part of any radiology or 'neuro-care' set-up. The present document is a consensus statement of the Indian Society of Neuroradiology, prepared after reviewing the available data and working experience. It scientifically tries to answer many questions faced by neuroradiologists everyday in practice. It encompasses simple things such as which patients need to be imaged, what precautions are essential, the work-flows, cleaning of radiology equipment, how to carry out neuro-interventions in COVID-suspect patients, and what procedures/tests to avoid, or their alternatives, to minimise the spread of COVID infection both to the patients and health care personnel. As radiology set-ups can be large, every sub-speciality may have certain precautions which will not be covered in general guidelines, and this document tries to answer those for neuroradiologists. Carefully evolved Standards of Operating Procedure (SOPs) and guidelines are the need of the hour to guide in providing uninterrupted and adequate services to the needy without compromising the safety of the specialised work force and facilities involved.